The impact of metabolic disorders on management of periodontal health in children - Yunyan Zhang; Tong‐Chuan He; Hongmei Zhang (Wiley, 2024)
Abstract Periodontitis is a chronic inflammatory disease caused by plaque biofilm which shares risk factors with systemic chronic diseases such as diabetes, cardiovascular disease, and osteoporosis. Many studies have found increased prevalence and rate of progression of periodontal disease in children with common metabolic disorders. Although the causal relationship and specific mechanism between them has not been determined yet. The aim of this paper is to progress on the impact of metabolic disorders on periodontal health in children and the underlying mechanisms, which provides new evidences for the prevention and intervention of metabolic disorders and periodontitis in children.